2006
DOI: 10.5194/aab-49-64-2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ESR1, FSHB and RBP4 genes on litter size in a Large White and a Landrace Herd

Abstract: Abstract. The polymorphisms of ESR1, FSHB and RBP4 genes were detected by PCR-SSCP, PCR and PCR-RFLP in a Large White and a Landrace herd in Beijing, China and the influence of ESR1, FSHB and RBP4 on litter size traits was analyzed using three models. We found polymorphisms for the three genes in Large White besides for ESR1 and RBP4 genes in Landrace. The results showed that the most genotype effects are of ESR1 among these three genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
4
15
0
Order By: Relevance
“…Zhao et al (1998) found a retroposon in intron 1 of FSH that non-retroposon homozygote sows produced 2.53 piglets more than retroposon homozygote sows for TNB on the 1 st parity. On the contrary, recent study reported inversely association between piglet number and HaeIII-FSH locus in Polish pig line (Korwin-Kossakowsak et al, 2003), in Large White (Wang et al, 2006;Humpolicek et al, 2007). Microsatellite 5'-flanking FSH affected number at weaning, litter weight at weaning, average individual weight at weaning in Large White x Chinese Meishan F 2 (Li et al 2008).…”
Section: Fsh Polymorphisms Discovery and Associationmentioning
confidence: 84%
“…Zhao et al (1998) found a retroposon in intron 1 of FSH that non-retroposon homozygote sows produced 2.53 piglets more than retroposon homozygote sows for TNB on the 1 st parity. On the contrary, recent study reported inversely association between piglet number and HaeIII-FSH locus in Polish pig line (Korwin-Kossakowsak et al, 2003), in Large White (Wang et al, 2006;Humpolicek et al, 2007). Microsatellite 5'-flanking FSH affected number at weaning, litter weight at weaning, average individual weight at weaning in Large White x Chinese Meishan F 2 (Li et al 2008).…”
Section: Fsh Polymorphisms Discovery and Associationmentioning
confidence: 84%
“…One marker, which is used in commercial pig production, is the estrogen receptor gene 1 (ESR1), and ROTHSCHILD et al (1996) were the first who observed an association between ESR1 genotypes and litter size in swine. However, so far, there are a lot of inconsistent studies with regard to influence on the ESR1 gene on fecundity parameters in swine (SHORT et al, 1997;DEPUYDT et al, 1999;DRÖGEMÜLLER et al, 1999;KMIEĆ et al, 2002;GIBSON et al, 2002; VAN RENS and VAN DER LENDE, 2002;MATOUŠEK et al, 2003;GOLIÁŠOVÁ and WOLF, 2004;HORÁK et al, 2005;HOROGH et al, 2005;WANG et al, 2006). Therefore, additional candidate genes with potential influence on litter size are studied.…”
Section: Introductionmentioning
confidence: 99%
“…of pigs bred in the USA, Europe and Asia (Drögemüller et al 2001;Kmieć et al 2002;Terman et al 2006;Wang et al 2006;Wu et al 2006). The breeding potential of gilts is determined by many factors and fully reveals itself after reaching sexual maturity and giving birth to the first and further litters.…”
Section: Discussionmentioning
confidence: 99%